THE POLITICS OF BANKING: GLOBALISATION AND DOMESTIC POLICY CHANGE - Sukarman, Widigdo (Journal of Indonesian Economy and Business, 2009)
The current article aims to elaborate on the history of bank policy modifications as a response towards economic and financial change, mainly due to globalisation. The centralstatus of banks in the economy causes a need for the government to protect it in many forms that differ from one country to another. Bank policy makers that are closed oresoteric and are short-lived must be opened up to be able to receive long term ideas. The process is also marked intensively with competing interests between other actors of the government.Keywords: esoteric, globalisation, segmentation, deregulation, problem of coordination